SUSTAINABLE TOURISM AND ECOLOGICAL APPROACHES: A CASE STUDY OF KOKAND CITY - Turgunov, Jasurbek (University Research Base, 2025)
Ecotourism and sustainable tourism have similar objectives to link conservation goals, and economic and rural development. Ecotourism offers educational and new experiences to tourists, requiring environmentally sensitive management to protect natural sites. The increase in eco-tourists in Uzbekistan has led to a rise in tourism agencies claiming to be ecotourism providers, often without specific guidelines or regulations. The findings will help identify the best practices for ecotourism in Uzbekistan toward sustainability. Sustainable tourism is crucial in preserving natural resources while fostering economic and social development. This paper explores Kokand City’s potential as an eco-tourism destination and highlights the sustainable business model of “Mehrigiyo,” a leading company. The study analyzes ecological approaches in tourism and sustainable production, demonstrating how local enterprises can contribute to environmental preservation while promoting cultural and natural heritage.